THE EFFECT OF AUDIO-VISUAL BASIC LIFE SUPPORT CHOKING EDUCATION IN TODDLERS ON PARENTS' KNOWLEDGE IN HANDLING CHOKING IN PAUD/TK BANGSA PLUS - rizky meuthia pratiwi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
An emergency condition is a life-threatening condition, in choking conditions a narrowing of the respiratory tract can occur which can be life-threatening. For choking incidents to be minimized, of course, one of the supporting factors is knowledge and skills. Inadequate parental knowledge in handling choking results in inaccuracies in handling. This study used a pre-experimental design technique with a one-group pre-test-post-test design approach. Data collection used a questionnaire and data analysis using the Wilcoxon test. The results showed that the majority of respondents had a sufficient level of knowledge about handling choking toddlers before being given audio-visual education, namely 46 people (92%) and 4 (8%) respondents had good knowledge, and no some are less knowledgeable. After the intervention was carried out, the result was that all respondents had a good level of knowledge after being given education, namely 50 people (100%). The results of bivariate analysis using the Wilcoxon test obtained a p-value of 0.000. In conclusion, there is an effect of basic life support choking audio-visual education on toddlers' knowledge on parental knowledge in handling choking toddlers in Kindergarten Bangsa Plus of the nation plus. The researcher concluded that this study gave significant results and had an impact on the knowledge and skills of parents, both fathers, and mothers, who are equally responsible for keeping children safe